ANALISIS PENYIMPANAN SISTEM KEARSIPAN DALAM MENDUKUNG PENGELOLAAN INFORMASI PADA BIRO KESEJAHTERAAN RAKYAT SEKRETARIAT DAERAH PROVINSI JAWA TIMUR - Farda Wulandari; Alif Faizah Qurota A’yun; Imelsya Afra Nabila Zahra; Silvi Nur Afifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Orderly and systematic archive management is an essential element in supporting the effectiveness of information management and administrative order within the government environment. This research aims to analyze the archival storage system and the process of transferring inactive archives in support of information management at the Bureau of People's Welfare, Regional Secretariat of East Java Province. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out thru direct observation and in-depth interviews with archive managers and relevant parties. The research results show that procedurally, the archive storage system has adhered to archival regulations, from file submission and verification, archive registration and classification, active archive storage, to the transfer of inactive archives based on the Archive Retention Schedule (ARS). However, in its implementation, various obstacles are still found, especially limitations in storage space, delays in transferring inactive archives, and a lack of optimal understanding of archival techniques. This condition leads to an accumulation of archives and potentially hinders information retrieval processes, as well as decreasing the effectiveness of administrative services. This research confirms that optimizing the archival system requires consistent application of procedures, improved human resource competency, and adequate infrastructure support to ensure information management can be carried out effectively, efficiently, and accountably.